Phylogenetics of tribe Exaceae (Gentianaceae) based on molecular, morphological and karyological data, with special emphasis on the genus Sebaea.: Taxonomic treatment of Exochaenium, Lagenias and the new genus Klackenbergia - Kissling, Jonathan (My University, 2007)
In an attempt to understand the evolutionary history of the poorly studied genus Sebaea and its relationship to other genera of tribe Exaceae (Gentianaceae), intensive morphological and karyological character optimization based on robust molecular phylogeny was performed. Phylogenetic reconstructions support the monophyly of Exaceae, and further reveal a polyphyletic Sebaea, including four well-supported clades, hereafter treated as separate genera, based on non-molecular synapomorphies. The first clade contains the single species Lagenias pusillus, characterized by its medifix anthers, inserted at the base of the corolla tube and its seed testa cells (polygonal). The second clade, Sebaea s. str., contains most of the South African species having secondary stigmas and bilateral seeds, with rectangular testa cell. The third clade, Exochaenium, contains exclusively tropical African species, characterized by a stylar polymorphism and a papillose clavate stigma (versus smooth and bilobed). Finally the fourth clade, Klackenbergia, contains two species characterized by inflorescences with axillary subsessile flowers. Based on these results, the taxonomic reinstatement of Exochaenium (23 species) and Lagenias (1 species), along with the establishment of a new genus Klackenbergia (2 species), are proposed. In the light of the new phylogenetic relationships found within the Exaceae, new views on the evolution of (1) karyological and (2) morphological characters are proposed. Finally, the historical biogeography of the tribe is reevaluated (3). 1. Intensive chromosome counts based on material collected and fixed in the field (157 population and c. 60 species), and exhaustive literature survey, reveal a broad set of chromosome numbers (2n = 18, 28, 32, 34, 36, 42, 52, 54, 56, 60, 62, 64, 68), and the occurrence of polyploid systems within Exacum and Sebaea. These results allow us to postulate x = 7, 8, or 9 as the possible base chromosome numbers for the Exaceae. Karyological reconstruction, based on the molecular phylogeny, suggest a basic number of x=7 for the Exaceae, followed by dysploidy event leading to secondary base number of x=8 and x=9, and several polyploidization events. 2. Optimization of morphological characters suggests that the most recent common ancestor of Exaceae (MRCA) was similar to Lagenias pusillus by having pentamerous yellow actinomorphic flowers, with anthers included in the corolla tube and dehiscing by longitudinal slits, a bilobed stigma, and the absence of secondary stigmas, and cubical seeds with polygonal testa cells. This MRCA might have then developed particular floral syndromes as indicated by long corolla tubes or presence of enantiostyly in the tribe. 3. Dating analyses and dispersal-vicariance reconstructions suggest that the Exaceae evolved c. 32 million years ago in Africa and subsequently spread to Madagascar. The colonization of Australia, New-Zealand, and Asia involved at least three long-distance dispersals. Early diversification of Exaceae in Africa might be the consequence of the development of a temperate with dry summer climate, in the Cape region (South Africa), while the Quaternary climatic variation might explain most of the species diversity of Sebaea and Exochaenium. At the generic level, molecular phylogenies of Sebaea, based on chloroplastic and nuclear DNA markers, reveals five well-supported clades. Sebaea sulphurea seems to have evolved early, and is distinct from all the remaining extant species. Each clade is supported by several characters (morphological, vegetative, phenological or geographical), and a preliminary infrageneric classification is proposed.
Thèse de doctorat : Université de Neuchâtel, 2007
Keywords: Africa; Exaceae; Belmontia; biogeography; chromosome numbers; Exacum; Exochaenium; Gentianaceae; Gentianothamnus; Gynoecium; karyology; Klackenbergia; Ornichia; Madagascar; Lagenias; Parasia; phylogeny; polyploidy; Sebaea; seed; stigma; systematics; Tachiadenus; taxonomy